Utilization of Serial Drawing Media as a Learning Tool for Narrative Writing in Elementary School - Rismayanti, Noni; Dewi, Resnita; Tanduk, Rita (Jurnal Kependidikan Media, 2024)
Writing is a very important language skill for elementary school students, especially in composing narrative essays. However, many students experience difficulties in writing narratives due to lack of ideas, limited vocabulary, and uninteresting learning methods. One of the alternatives to improve narrative writing skills is by utilizing serial image media as a learning tool. Serial drawing media can help students understand the storyline more systematically, increase their imagination, and enrich their vocabulary in writing. This study aims to explore the utilization of serial picture media in improving the narrative writing ability of elementary school students. This research was conducted at SD Negeri 10 Pakassasan, Mamasa, using a qualitative approach. Data were collected through observations, interviews, and document analysis to understand how the use of serial image media contributes to the learning of narrative writing. The results showed that the use of series picture media had a positive impact in increasing students' motivation and writing ability. Students find it easier to develop ideas, organize a coherent storyline, and improve the quality of their writing. In addition, this media also helps teachers in creating more interactive and fun learning. Thus, the utilization of serial image media can be an effective solution in overcoming narrative writing problems in primary schools, especially in rural areas such as Mamasa.